Study on The Determination of Chitosan Functional Groups of Sotong (Sepia sp ) Bone Extract - Tasya D.P. Br Sihotang; Inneke F.M. Rumengan; Stenly Wullur; Darus S.J. Paransa; Nickson J. Kawung; James J.H. Paulus (Sam Ratulangi University, 2025)
Chitosan of cuttlefish (Sepia sp). from North Sulawesi waters has never been reported yet. This study aims to (1) modify cuttlefish bone chitin into chitosan; (2) determine the yield of chitosan of cuttlefish bone raw materials; (3) determine the functional groups of chitosan obtained from cuttlefish bone using the FTIR analysis method. Samples of cuttlefish bone were collected from several locations, dried, and grinded. The steps of extraction of chitin consisted of demineralization with 1.5M HCl for 72 hours, neutralization with distilled water, deproteination with 3.5% NaOH solvent and heating at 600C for 4 hours, and then neutralization again and drying. Modification chitin to chitosan was conducted by deacetylation with 60% NaOH at 1100C for 4 hours. The results showed that the yield of chitosan was about 3.8%. The chitosan was then subjected to FTIR, and the results indicated that functional groups of the chitosan molecule, namely the -NH, -CH, CC-, -OH and -C=O groups, are in the wavelength range corresponding to the wavelength range of the standard chitosan molecule, with slight variations, especially in the -NH group. It can be concluded that the cuttlefish bone chitosan meets the criteria for functional groups of standard chitosan. Keywords: chitosan, cuttlefish bone, FTIR, deacetylation Abstrak Kitosan dari tulang sotong (Sepia sp). asal perairan Sulawesi Utara belum pernah dilaporkan sebelumnya. Penelitian ini bertujuan untuk (1) memodifikasi kitin tulang sotong menjadi kitosan; (2) mengetahui rendemen kitosan dari bahan baku tulang sotong; (3) mendeterminasi gugus fungsi kitosan dengan metode analisis FTIR. Sampel tulang sotong dikoleksi dari beberapa lokasi, dikeringkan dan digerus. Tahap-tahal ekstraksi kitin terdiri dari demineralisasi dengan HCl 1,5M selama 72 jam, netralisasi dengan akuades, deproteinasi dengan NaOH 3,5% dan pemanasan pada suhu 600C selama 4 jam, kemudian netralisasi dan pengeringan. Moodifikasi kitin menjadi kitosan dilakukan dengan deasetilasi dengan NaOH 60% dan dipanaskan pada suhu 1100C selama 4 jam. Hasil penelitian menunjukkan bahwa rendemen kitosan yang dihasilkan sekitar 3,8%. Kitosan yang diperoleh kemudian dilakukan pengujian FTIR, ternyata hasilnya menunjukkan bahwa gugus fungsi molekul kitosan, yaitu gugus -NH, -CH, CC-, -OH dan -C=O, berada pada rentang panjang gelombang yang sesuai dengan rentang panjang gelombang molekul kitosan standar, dengan sedikit variasi terutama pada gugus -NH. Dengan demikian dapat disimpulkan bahwa kitosan tulang sotong yang diteliti memenuhi kriteria gugus fungsi kitosan standar. Kata kunci: kitosan, tulang sotong, FTIR, deasetilasi